Setting up Shop: Self-Employment among Canadian College and University Graduates - Finnie, Ross; Laporte, Christine (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2003)
AbstractThis article reports the results of an empirical analysis of self-employment among recent college and university graduates using the National Graduates Survey databases. It finds that self-employment rates two years after graduation, calculated by year of graduation (1982, 1986, 1990 and 1995) and level of education, ranged from 6.5 percent to 7.8 percent for men, and from 3.2 percent to 5.2 percent for women. Five years after graduation, the rates had increased, ranging from 9.9 percent to 11.1 percent for men, and from 5.3 percent to 6.7 percent for women. The evidence regarding employment rates, job satisfaction, the job-education skill match and earnings (the latter including the estimation of both cross-sectional and fixed effects models) suggests that self-employment is generally associated with enhanced labour market outcomes—that is, the result of “pull” factors. Policy implications are discussed.